An autoethnography of the feminist pedagogical strategies used in teaching and learning to promote inclusive classrooms - Garutsa, Tendayi (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
Although institutions of higher learning in South Africa have made progress in policies and programming that curb the ideological hegemonic positions inflicted by the Apartheid education system, higher education is still grappling with gender inequalities and inequities in the classroom context. This article reflects on my journey and pedagogical experiences as a student and later a feminist lecturer. Feminist pedagogues are promising approaches for social transformation in institutions of higher learning. I focused on my experiences, exploring the tensions that have shaped my praxis. I employed an auto-ethnographic research approach through an autobiography research method to illustrate my experiences as I transitioned from being a student to a tutor and a feminist lecturer within institutions of higher learning in South Africa. Findings from this paper show that to disrupt normative classrooms, lecturers need to harness classroom strategies that can enhance inclusion, equity, social justice, and equality. These might include but are not limited to reflexive journaling, negotiating, and listening, dialogue, mutual vulnerability to challenge conventional power relations in institutions of higher learning. The article recommends that feminist pedagogy can work towards solving potentially unequal relations and discriminatory learning environments. This can be done by disrupting normative power hierarchies in the classroom by allowing both lecturers and learners to negotiate the process of ‘being listened to and ‘being heard in the teaching and learning environments and thus creating room for plural voices and more inclusive learning spaces.
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 7 (2) (2023)
Keywords: Feminist Pedagogy; Gender roles; Auto- Ethnography; Higher Education; Feminist anthropology; Inclusive education; Education, Higher -- South Africa; Feminism; Teaching -- South Africa